Don't Touch that Flower - Hemming, Alice; Slater, Nicola (Naperville, Illinois : Sourcebooks Jabberwocky, 2023)
"Squirrel is apprehensive about the arrival of Spring until he spots a wildflower and tries to claim it as his own, not understanding his overbearing protectiveness is doing more harm than good. Includes information on flowers."--
Keywords: Squirrels -- Juvenile fiction; Birds -- Juvenile fiction; Animals -- Juvenile fiction; Spring -- Juvenile fiction; Flowers -- Juvenile fiction; Squirrels -- Fiction; Birds -- Fiction; Animals -- Fiction; Spring -- Fiction; Flowers -- Fiction; Picture books